Book review: Islam, S. and Hossain, I. 2016: Social Justice in the Globalisation of Production: Labor, Gender, and the Environment Nexus. (April 2017) - Hansda, Regina
Islam, S. and Hossain, I. 2016: Social Justice in the Globalisation of Production: Labor, Gender, and the Environment Nexus . London: Palgrave Macmillan, International Political Economy Series. Xvi + 206 pp. $109.00 (hardcover). ISBN: 978-1-137-43400-5.